Labor in crisis : - Brody, David (J. B. Lippincott, 1965)
The steel strike of 1918 was a turning point industrial history that did not turn, a tremendous unionizing effort that failed. Here David Brody analyzes that tense time and seeks to explain what there was in the 1918 situation that made failure inevitable.